Lignin-coated polystyrene/trichloromethylsilane absorbent for oil spill cleanup - Nur Amalina Azhar,; Nadia Adrus,; Wan Aizan Wan Rahman,; Rohah A. Majid, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The study was conducted to determine the effectiveness of lignin-polystyrene/ trichloromethylsilane (TL-PS) absorbent in removing oil spillage from wastewater. Lignin powder obtained from the delignification of oil palm empty fruit bunch (OPEFB) was coated with PS emulsion (PSE) at various concentrations (2, 4, 6, & 8 mL) in order to bind the powder into an aggregated form. Later, L-PS was exposed to trichloromethylsilane (TCMS) via chemical vapour deposition method (CVD) at fixed 7.5 min exposure time to form TL-PS absorbent. The wettability of TL-PS was determined by conducting water contact angle (WCA) measurement and oil sorption capacity. It was found that TL-PS4 sample (immersed in 8 mL PSE) had the highest WCA value (134.10°) and oil sorption capacity (52%) in comparison with L-PS4 (immersed in 8 mL PSE without TCMS) with WCA value of 99.10° and oil sorption capacity of 40%. Meanwhile, the disappearance of hydroxyl group (OH) at peak 3429 cm-1 and appearance of siloxane bonds (R-Si-O) at peak in range of 1000 - 1100 cm-1 and 3.9 - 4.0 ppm had confirmed the substitution occurred between these groups, as shown by the spectra obtained from attenuated total reflectance-Fourier transform infrared (ATR-FTIR) and nuclear magnetic resonance (NMR). Thermal stability of TL-PS4 (onset degradation temperature at 252 °C) was higher when compared with lignin (onset degradation temperature at 40 °C), as showed by the thermogravimetric analysis (TGA). Meanwhile, the surface of absorbent had change from smooth (L-PS4) to rough (TL-PS4) corresponding to the deposition of silane particles onto the surface of L-PS after the exposure with TCMS, as shown by the scanning electron microscopy (SEM). The results suggested that TL-PS has a promising potential to be used as an absorbent for oil spill cleanup.